Blaming the Jews : politics and delusion - Harrison, Bernard 1933- (Studies in antisemitism, 2020)
"In recent years Western countries have seen a proliferation of antisemitic material in social media and other online outlets and in violent attacks on Jews. The evidence is undeniable, ranging from FBI hate-crime statistics to the attack on Tree of Life Synagogue in Pittsburgh in 2018. In Blaming the Jews, author Bernard Harrison offers a new and unique analysis of the nature of antisemitism and its persistence as a cultural phenomenon. Questioning the assumption that antisemitism affects or targets only Jews, he demonstrates that, allowed to go on unrecognized or unchecked, antisemitism is potentially damaging to us all. In a world where rhetoric is fashioned on stereotypes, Harrison argues it is our responsibility to be vigilant in exposing the delusions of antisemitism that have potentially appalling consequences for Jews and non-Jews alike"--